SURGE-ahead postoperative delirium prediction: external validation and open-source library - Kocar, Thomas; Wolf, Philip; Leinert, Christoph; Brefka, Simone; Fotteler, Marina L.; Uihlein, Adriane; Wezel, Felix; Wehling, Martin; Rahbari, Nuh; Kestler, Hans; Gebhard, Florian; Dallmeier, Dhayana; et al. (European geriatric medicine, 2025)
To externally validate the performance of the SURGE-Ahead postoperative delirium (POD) prediction algorithm in older adults undergoing surgery.